Potret Praktik Good Governance Dalam Meningkatkan Kinerja Bumdes Maju Rahayu Jatirunggo - Mandi’, Darmayanti; Maria, Evi (Center for Accounting Development and Research (CARD) Program Studi Akuntansi – Fakultas Ekonomika dan Bisnis Universitas Kristen Satya Wacana, 2025)
This research aims to photograph good governance practices in a village-owned enterprise (BUMDes) Maju Rahayu, Jatirunggo. An interpretive paradigm with a case study method was used in this research. Research data comes from informants participating in BUMDes management activities and the Jatirunggo Village community. The research results found that BUMDes are managed by applying the principles of good governance, including community participation, transparency, accountability, responsiveness, law enforcement, effectiveness and efficiency, equality, consensus orientation, and strategic vision. Implementing this principle is the key to successfully improving the performance of BUMDes Maju Rahayu. However, there are still several applications of good governance principles that still need to be optimal there. This occurs because limited human resources mean that multiple positions are still being held, difficulties in identifying and recording BUMDes financial transactions, accountability reporting, and work plans to residents have not been carried out using internet technology and websites, as well as a lack of commitment from the community, BUMDes managers and village governments to participate in BUMDes business activities actively. Therefore, BUMDes still needs to make efforts to increase human resource capabilities through training in management, finance, and mastery of information technology, as well as adding additional employees, if necessary.